# Quadratic Equation: How To Solve Using Factorization Method

This article will give you a detailed explanation of quadratic equations, their meaning, and different methods of solving them using the factorization method. Ensure that you read this article to the end to be fully acquainted with the easy steps for solving quadratic equations.

At the end of this article, you will be able to solve simple and complex problems involving simultaneous equations using the factorization method. You will also know when to use it and when to use other methods of solving simultaneous equations.

A quadratic equation has the highest power of the unknown of 2. This indicates that you will have two unknown values that will satisfy the equation when you check. The unknown values are sometimes called the roots of the equation.

The quadratic equation takes the general formula of:

ax2 + bx + c = 0

Where;

a, b and c are constant such that a≠0. If a = 0, then it is not a quadratic equation.

The following are some examples of a quadratic equation:

X2 + 7x + 10 = 0

X2 – x – 20 = 0

4x2 = 9

(x-1)(x-2) = 0

(x+2)2 = 25

The above examples all follow the general quadratic equation formula of ax2 + bx + c = 0. What actually makes an equation quadratic is the value of the highest power of the unknown (x in our case), which should not be greater than 2.

### How Do I Solve Quadratic Equations?

There are four (4) ways to solve a quadratic equation. They include the following:

• Factorization method
• Completing the squares
• Formula Method
• Graphical Method

Each of the above methods can solve a wide range of quadratic equations. In this article, however, we are going to focus on solving quadratic equations using the factorization method. We will try to solve different exercises to ensure your mastery of the topic, and we will also highlight the limitations of the factorization method.

### Factorization Method Of Solving Quadratic Equation

Factorization involves simplifying an equation using common factors of the equation. When we consider the general quadratic equation of ax2 + bx + c = 0, the factorization method will involve expressing this given equation as two linear factors (x + m) and (x + n) in such a way that ax2 + bx + c = (x + m)(x + n) = 0. These factors can further be explained as:

If (x + m)(x + n) = 0

Then; x + m =0……………………………….(1)

x + n = 0………………………………..(2)

The solutions of these two linear equations give the solution of the quadratic equation as they satisfy the values of the unknowns.

#### Example 1

Solve the quadratic equation x2 – 4x -12 = 0 using the factorization method

##### Solution

x2 – 4x – 12 = 0

STEP 1: Find two common factors that, when simplified, give the quadratic equation in question. You can do this easily by multiplying the integer with the unknown that has power, which is x2 multiplied by -12. List all the common multiples of -12 and select one in which you will get the middle term (-4x) if you simplify. The two multiples are +2 and -6.

Therefore, in the equation above, the factors are (x + 2) and (x – 6).

STEP 2: Express the factors in an equation form

(x + 2)(x -6) = 0

Note that when you expand this equation, you will get the quadratic equation x2 – 4x – 12 = 0, which means that the factors are correct.

STEP 3:

From the equation, (x + 2)(x -6) = 0

Either x +2 = 0

Or x – 6 = 0

Therefore, x= -2 or +6

#### Example 2

Solve the quadratic equation (x -4)(x +5)=0

##### Solution

The expression (x -4)(x +5) has already been factorized, so you can simplify it to get the two values of the unknown.

(x -4)(x +5) = 0

Either x -4 = 0

x = 4

or x + 5 = 0

x = -5

Therefore, x = 4 or -5

How To Solve Simultaneous Equations

#### Example 3

Solve the given quadratic equation (x + 2)2= 0 using Factorization method

##### Solution

There are two ways to solve this; one is very easy and straightforward. We shall proceed with the longer method before proceeding with the easy method.

(x + 2)2= 0

Step 1= Open Bracket

(x + 2)2= 0

X2 + 4x + 4 = 0

Step 2: Get the two common factors of the equation

The two factors are +2 and +2

(x + 2)(x+2) =0

Either x + 2 = 0

X = -2

0r x + 2 = 0

x = -2

Therefore, the two values of the unknown are -2 and -2.

Alternatively, you can solve it this way

(x + 2)2= 0

This can be written as;

(x + 2)(x + 2) =0

You can then go ahead and complete the solving.

#### Example 4

Using the Factorization method, solve the quadratic equation 2x2 + 6x = 0

##### Solution

You have to find the two factors of the equation

2x2 + 6x = 0

2x(x+3) = 0

Either 2x = 0

x = 0/2

=0

Or x + 3 = 0

x = -3

Therefore, x = 0 or -3

#### Example 5

Solve the equation, x2 = 9

##### Solution

x2 = 9

Move all the numbers to the left-hand side of the equation, leaving only zero on the right-hand side before factorization

x2 – 9 = 0

Factorize using the difference of two squares

Recall, x2  – 9 = x2 – 32

x2 – 32 = 0

(x-3)(x+3) = 0

Either x – 3 = 0

x = 3

or x + 3 = 0

x = -3

Therefore, x = 3 or -3

### Limitations Of Factorization Method of Solving Quadratic Equation

The factorization method has some significant limitations:

• It cannot solve all quadratic equations, as not all equations can be factorized.
• When the coefficient of the unknown has many factors, it becomes more difficult to list all the factor pairs you need to solve the equation.

NOTE: Always be mindful of the negative signs when carrying out factorization.

This article clearly demonstrates how to solve a quadratic equation using the factorization method. If you have any questions, please use the comment section below.

Also, endeavour to subscribe to this blog using your email in the comment section below. Do visit regularly for education guides.